Intra and Extrahepatic Congenital Dilatation of the Bile Ducts,. Caroli's Disease·. Hepatic - Jejunostomy - Davidenko, Nicolás; Casanova de Davidenko, Marys; Sotelo, José R; Machado, Martha; Davidenko, Antonio (Cirugía del Uruguay, 1980)
One case of intra and extrahepatic congenital dilatation fo the biliary tree ass'ciated to a pigmentary . biliary lithiasis is reported. First was treated by cholecystectomy ( gallstOnes,). 6 years later began with recurrent cholangitis due to choledocholithiasis. 2,74 A side to· side hepatic - jejunostomy was performed with an Hivet - Warren - Praderi loop. 17 months later ·the patient remains asyntomatic. Erectronic microscopy confirmed the diagnosis.